Utilização de quitosana e piperina na alimentação de animais: análise da eficácia no reparo de lesões cutâneas em ratos - (:unkn) unknown (Universidade Brasil, 2024)
The skin, known as the largest organ in the human body, stands out for its unique role in maintaining the integrity of the organism. Disruptions in the epithelial layers are called skin lesions or wounds. Wound repair consists of a mechanism consisting of the phases of hemostasis and inflammation, proliferation and remodeling, starting immediately after the injury occurs. The need for efficient therapy to care for a population affected by injuries is a growing challenge that demands innovative, efficient and affordable strategies. In this scenario, the present study aims to the evaluation of the association of the antimicrobial and reparative action of Chitosan (Chi) with the anti-inflammatory action of Piperine (PIP) in the process of repairing skin lesions. To this end, lyophilized microparticles of Chi and PIP were produced and characterized for subsequent administration to animals with lesions induced via gavage. After freeze-drying, 2.4g of QUI and 2.7g of Chi/PIP were obtained. The spectra obtained through Fourier Transform Infrared Spectroscopy (FTIR) showed vibration bands characteristic of the chemical groups that form the material and corroborate the literature. Scanning electron micrographs (SEM) of the powdered samples showed particles with relatively rough surfaces, while the freeze-dried samples presented thinner surfaces with greater surface area. Both materials do not present a thermal degradation process at temperatures below 60ºC, indicating that they remain active (not degraded) when subjected to animal body temperature. The qualitative analysis of the lesions, obtained from in vivo results, revealed no signs of necrosis, odor or liquid in the lesion cavity, nor did it indicate the presence of fibrosis. The morphometric analysis of the wound repair index showed no statistically significant difference between the experimental groups in all periods studied. Likewise, through histological analysis of the injured tissue, it was not possible to observe significant changes between the experimental groups.
Keywords: Quitosana; Piperina; Liofilização; Gavagem; Lesões cutâneas; Engenharia Biomédica (Bioengenharia)